2020
DOI: 10.1136/oemed-2020-106522
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer mortality in the French cohort of titanium dioxide workers: some aetiological insights

Abstract: ObjectivesTitanium dioxide (TiO2) is widely used in construction, food, cosmetic and medical industry. The current evidence on TiO2 carcinogenicity in humans is considered inadequate. As French participants of the European cohort of TiO2 workers exhibited an increase in mortality from lung cancer, we aimed at investigating whether TiO2 exposure, co-exposures or smoking can explain this increase.MethodsWe reanalysed the data of 833 French male workers (follow-up period 1968–1997) and used multiple imputation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…Prior to undertaking the g-formula analysis, we assessed the most important HWSE components in these data and confirmed their presence. Moreover, prior reports of SMR analyses indicated patterns consistent with the HWSE3 and in the analysis of the French cohort, duration of employment was negatively associated with lung cancer mortality 2. These underscore the relevance of g-methods in these cohorts and future investigations of TiO 2 ’s effects on human health.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Prior to undertaking the g-formula analysis, we assessed the most important HWSE components in these data and confirmed their presence. Moreover, prior reports of SMR analyses indicated patterns consistent with the HWSE3 and in the analysis of the French cohort, duration of employment was negatively associated with lung cancer mortality 2. These underscore the relevance of g-methods in these cohorts and future investigations of TiO 2 ’s effects on human health.…”
Section: Discussionsupporting
confidence: 55%
“…The exchangeability assumption (ie, no unmeasured confounding) is challenging given the limitations of available data on smoking. The most complete smoking data were available for the French cohort and showed no effect of adjustment for smoking on estimates of TiO 2 -lung cancer mortality associations 2. Moreover, we were able to assess some other occupational coexposures that are suspected or known lung carcinogens, including asbestos, welding fumes and other mineral dusts; adjustment for these exposures had no effect on the association with TiO 2 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Obviously, this also affects the number of unexposed and exposed workers as reported in the supplemental Table S3. 2 We recognize that we should have specified this also in the footnotes of that table.Regarding tobacco smoking, data were available for 201 (not only 33) workers at the second French plant and the combined crude smoking prevalence for the two French plants was 34%, compatible with the age-standardized prevalence of 42% reported by Boffetta et al 1 As discussed in our paper, 2 we recognize that the reported prevalence of smoking was low, and lower than that estimated on the national level.…”
mentioning
confidence: 99%
“…Obviously, this also affects the number of unexposed and exposed workers as reported in the supplemental Table S3. 2 We recognize that we should have specified this also in the footnotes of that table.…”
mentioning
confidence: 99%